(untitled) (Annals of Medical Research, 2021)
Aim: In this study the aim was to compare internalized stigmatization and quality of life between bipolar disorder and schizophrenia patients who were in remission.Material and Methods: Patients who were admitted to the psychiatry outpatient clinic of Gaziantep University Faculty with a diagnosis of bipolar disorder or schizophrenia according to DSM-5 were included in this cross sectional study. Assessment tools were the Internalized Stigma of Mental Illness Scale and the World Health Organization Quality of Life Measurement Instrument Short Form.Results: Schizophrenia and bipolar disorder groups were compared according to assessment tools. 58 bipolar disorder and 52 schizophrenia patients were included in the study. The Quality of Life of patients with bipolar disorder was found to be higher than patients with schizophrenia according to mental domain (p = 0.006) and social relationships domain (p = 0.050). Internalized Stigma of schizophrenia patients was higher than patients with bipolar disorder (p = 0.030). Internalized Stigma was higher in female patients with schizophrenia than female patients with bipolar disorder (p = 0.006). There were no significant differences between male schizophrenia patients and patients with bipolar disorder according to quality of life. Conclusion: Internalized stigmatization is a problem that should be considered in schizophrenia patients, especially in female schizophrenia patients. Internalized stigmatization may result in decreased quality of life in schizophrenia.